Iridium complexes catalysed the selective dehydrogenation of glucose to gluconic acid in water. Issue 17 (10th August 2018) - Borja, Pilar; Vicent, Cristian; Baya, Miguel; García, Hermenegildo; Mata, Jose A.
Abstract : A catalytic dehydrogenation process for the production of gluconic acid from glucose and starch is reported here. Abstract : We describe an unprecedented catalytic dehydrogenation of glucose by homogeneous catalysts. Iridium(iii ) complexes containing the fragment [Cp*Ir(NHC)] 2+ (NHC = N-heterocyclic carbene ligand) are shown to be very active and highly selective catalysts for the dehydrogenation of glucose to gluconic acid and molecular hydrogen. Glucose is converted to gluconic acid at a catalyst loading of 2 mol%, at reflux in water, without additives and with a selectivity of over 95%. Experimental evidence obtained by 1 H NMR spectroscopy and mass spectrometry (ESI/MS) reveals the formation of iridium coordinated to glucose and gluconic acid species. A plausible mechanism is proposed, based on the experimental evidence and supported by DFT calculations.